Introduction of HPV vaccination in Kenya - Vermandere, Heleen (Afrika Focus, 2016)
HPV vaccination prevents cervical cancer, the fourth most common cancer among women worldwide. Measured HPV vaccine acceptability is often high but does it also lead to high uptake? Methodology: A cohort was set up assessing HPV vaccine acceptability and other health behav- iour constructs before, and vaccine uptake after an HPV vaccination programme in Eldoret, Kenya. Focus groups shed light on the motivation for vaccine uptake or refusal. Results: Acceptability was high but was no strong predictor of uptake, and neither were the constructs of the Health Belief Model. Lack of information and fear of side effects were major barriers. Feeling uncomfortable to discuss cervical cancer hampered open communication. Discussion: Distrust towards new vaccines and the health system blocked translation from willingness-to-vaccinate to actual uptake, as did organizational factors such as poor promotion. Conclusion: Future research should include broader concepts such as vaccine hesitancy and factors beyond personal control in order to predict vaccine uptake. Key words: HPV vaccination, acceptability, uptake, longitudinal study, Kenya